The Modern Girl : Feminine Modernities, the Body, and Commodities in the 1920s - Nicholas, Jane, 1977- (Book collections on Project MUSE., 2015)
Using a wide range of visual and textual evidence, Nicholas illuminates both the frequent public debates about female appearance and the realities of feminine self-presentation in 1920s Canada.